2010
DOI: 10.4103/1463-1741.64973
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular evoked myogenic potential in noise-induced hearing loss

Abstract: Noise affects one's hearing as well as balance mechanism. The hearing mechanism of the noise-exposed individuals has been extensively studied. However, in view of the poor research focus on the sacculo-collic reflexes, especially in this study area, the present study was undertaken to examine the vestibular evoked myogenic potentials (VEMP) in subjects with noise-induced hearing loss (NIHL). A total of 30 subjects (55 ears) with NIHL participated in the present study within the age range of 30-40 years. VEMP r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
35
2
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 10 publications
9
35
2
2
Order By: Relevance
“…cVEMP latency results were in agreement with Kumar et al [15] , they reported that in NIHL, as the pure tone average increased, the latency was prolonged, also our results are in agreement with Wang and Young [16] who reported that an increasingly damaged saccule could result in abnormal VEMPs (e.g., absent or delayed VEMPs) in subjects with >40dB at 4 kHz. Similar results are also obtained by Tseng and Young [17] who reported that there was a decreasing order of abnormal percentages in the function of the cochlea, saccule, utricle, and semicircular canals after exposure to a chronic noise, this further supports that pars inferior (cochlea and saccule) is more vulnerable to noise damage than pars superior (utricle and semicircular canals).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…cVEMP latency results were in agreement with Kumar et al [15] , they reported that in NIHL, as the pure tone average increased, the latency was prolonged, also our results are in agreement with Wang and Young [16] who reported that an increasingly damaged saccule could result in abnormal VEMPs (e.g., absent or delayed VEMPs) in subjects with >40dB at 4 kHz. Similar results are also obtained by Tseng and Young [17] who reported that there was a decreasing order of abnormal percentages in the function of the cochlea, saccule, utricle, and semicircular canals after exposure to a chronic noise, this further supports that pars inferior (cochlea and saccule) is more vulnerable to noise damage than pars superior (utricle and semicircular canals).…”
Section: Discussionsupporting
confidence: 93%
“…According to Vetter [19] , these protective mechanisms have never been assessed as protective mechanism of the vestibular end organs again, this may raise our probability of the vestibular affection before the cochlear affection with chronic noise exposure. This study concluded that there was a significant decrease in the cVE-MP amplitude in relation to the control group, similar results were obtained by Kumar et al [15] ; while these results disagree with Emara and Gabr [20] who reported that there was statistically insignificant reduction of the cVEMP amplitude with increase of the duration and the degree of hearing loss.…”
Section: Discussioncontrasting
confidence: 51%
“…In humans, several studies, with relatively small sample sizes ( n  = 20-30), showed that abnormal (reduced, delayed or absent responses) cervical vestibular evoked myogenic potentials (VEMPs) and ocular VEMPs are associated with chronic or acute acoustic trauma [62, 131133]. This supports the hypothesis that noise causes functional damage to the otolithic organs either directly or indirectly.…”
Section: Beyond Hearing Loss: Associated Symptomatologymentioning
confidence: 87%
“…It has been reported that some individuals with noise-induced hearing loss (NIHL) also suffer from balance disorders (Oosterveld et al, 1982; Juntunen et al, 1987; Golz et al, 2001). Reduced vestibular caloric response (Manabe et al, 1995; Golz et al, 2001), reduced vestibular-evoked myogenic potentials (VEMP) (Wang et al, 2006; Wang & Young, 2007; Kumar et al, 2010; Akin et al, 2012; Zuniga et al, 2012), nystagmus (Man et al, 1980; Shupak et al, 1994; Oosterveld et al, 1982; Golz et al, 2001), and increased body sway (Ylikoski 1988; Kilburn et al, 1992) have been reported. Despite our understanding of the effect of noise on auditory function, the mechanisms underlying noise-induced vestibular deficiency remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%